2016
DOI: 10.1155/2016/3401272
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Methanogenic Communities in Different Laboratory-Scale Anaerobic Digesters

Abstract: Comparative analysis of methanogenic archaea compositions and dynamics in 11 laboratory-scale continuous stirred tank reactors fed with different agricultural materials (chicken manure, cattle manure, maize straw, maize silage, distillers grains, and Jatropha press cake) was carried out by analysis of the methyl coenzyme-M reductase α-subunit (mcrA) gene. Various taxa within Methanomicrobiales, Methanobacteriaceae, Methanosarcinaceae, Methanosaetaceae, and Methanomassiliicoccales were detected in the biogas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 59 publications
6
23
0
3
Order By: Relevance
“…4b), however, they disappeared in active populations and new genera including Methanosarcina and Methanosaeta, occurred, despite their low relative abundance in the 16S rRNA amplicon reads, which most likely be explained by the fact that the number of ribosome were much higher in active cells than that in dormant cells. 43 Previous studies demonstrated that Methanosaeta, a methanogenic archaea exclusively conducting acetoclastic methanogenesis, was negatively correlated with the total ammonium nitrogen concentration and kept increased activity under high organic acids concentrations, 44,45 which was in line with the increase in the relative abundance of Methanosaeta and the decline of total ammonium nitrogen concentration in the present study ( Fig. 4b, Table 1).…”
Section: Diversity Of Microbial Communitiessupporting
confidence: 89%
“…4b), however, they disappeared in active populations and new genera including Methanosarcina and Methanosaeta, occurred, despite their low relative abundance in the 16S rRNA amplicon reads, which most likely be explained by the fact that the number of ribosome were much higher in active cells than that in dormant cells. 43 Previous studies demonstrated that Methanosaeta, a methanogenic archaea exclusively conducting acetoclastic methanogenesis, was negatively correlated with the total ammonium nitrogen concentration and kept increased activity under high organic acids concentrations, 44,45 which was in line with the increase in the relative abundance of Methanosaeta and the decline of total ammonium nitrogen concentration in the present study ( Fig. 4b, Table 1).…”
Section: Diversity Of Microbial Communitiessupporting
confidence: 89%
“…Methanosaetaceae, the methanogens can survive at both high and low concentrations of acetate [57,58]. In both the mono-digestion and co-digestion process, Methanobacteriaceae was found in all stages and ranged from 12.02-20.44%, which is in the line with the work of Gagliano et al [59] and Ziganshin et al [60]. Methanobacteriaceae is the primary user of formate and H2/CO2 substrates for methane formation.…”
Section: Composition Of Archaeal Communitysupporting
confidence: 83%
“…The changes of intI1 representing the mobile genetic elements (MGEs) was followed to reflect the potential of HGT and multi-resistance (Engelstädter et al, 2016). The functional gene mcrA involved the methane production was quantified to reflect the effects of GO addition on the methanogenesis (Ziganshin et al, 2016).…”
Section: Qpcrmentioning
confidence: 99%